2004
DOI: 10.1155/s1110865704312060
|View full text |Cite
|
Sign up to set email alerts
|

ADAM: A Realistic Implementation for a W-CDMA Smart Antenna

Abstract: Adaptive-type smart antennas do not usually operate on the deployed universal mobile telecommunication system (UMTS) scenarios, although UTRA (UMTS terrestrial radio access) foresees their operation and they would improve capacity especially in mixed-service environments. This paper describes the implementation of a software radio-based version of an adaptive antenna, named ADAM, that can be used with any standard Node B, both in the up- and downlinks. This transparent operational feature has been made possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A detailed study on performance for smart antennas in W-DCMA systems can be found in [210]. Some simulation results based on the specific features of the adaptive antenna prototype presented here were shown in [211], [212]. Although they are not the objective of this thesis, the most interesting results are included here, in order to motivate the interest of implementation of this prototype.…”
Section: Simulation Results and Expected Performancementioning
confidence: 99%
See 1 more Smart Citation
“…A detailed study on performance for smart antennas in W-DCMA systems can be found in [210]. Some simulation results based on the specific features of the adaptive antenna prototype presented here were shown in [211], [212]. Although they are not the objective of this thesis, the most interesting results are included here, in order to motivate the interest of implementation of this prototype.…”
Section: Simulation Results and Expected Performancementioning
confidence: 99%
“…System-level simulations were also carried out to estimate the expected performance of an adaptive antenna as the one implemented here, in a cellular system [210], [211]. The total throughput per cell in the downlink was computed.…”
Section: Simulation Results and Expected Performancementioning
confidence: 99%